Large Unit Teaching Design of Chinese: dispute analysis, Integration and Evaluation Strategy - REN Mingman; WEN Yihan (Jiaoshi jiaoyu xuebao)
To design large unit teaching based on Chinese textbooks, it is essential to reflect on the feasibility and localization of large unit teaching, define its scope of implementation, and establish the connection between large unit and learning task groups, and textbook units. Refining key concepts for different types of textbook units involves fundamental strategies such as following the guidance of the core concept of the new curriculum standard, sorting out the consistency of humanistic themes, language elements and texts, pursuing the common agreement between language content and form, and directly facing the deviation and reconstruction of theme control and text characteristics. Transforming major concepts into common problems as the core of designing advanced learning tasks can achieve the consistency from the outside to the inside of large unit teaching. To evaluate the progress of large unit learning, it is necessary to combine process evaluation with summative evaluation, match appropriate evaluation methods according to the type of teaching objectives and learning task characteristics, and develop targeted evaluation tools.